Interaction of shallow cold surges with topography on scales of 100-1000 kilometers - Toth, James J., author; Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 1987)
A shallow cold air mass is defined as one not extending to the top of the mountain ridge with which it interacts. The structure of such an airmass is examined using both observational data and a hydrostatic version of the Colorado State University Regional Atmospheric Modeling System. The prime constraint on a shallow cold surge is that the flow must ultimately be parallel to the mountain ridge. It is found that the effects of this constraint are altered significantly by surface sensible heat flux. Cold surges are slowed during the daylight hours, a result consistent with previous observational studies in Colorado east of the Continental Divide. Two case studies are described in detail, and several other events are cited. Since observations alone do not provide a complete description of diversion of the cold air by the mountain range, numerical model simulations provide additional insight into import ant mechanisms. A case study on 14 June 1985 is described using observational and model data. The model development of a deep boundary layer within the frontal baroclinic zone is consistent with the observations for this and other cases. This development is due to strong surface heating. Turning off the model shortwave radiation is seen to produce a rapid southward acceleration of the surface front, with very shallow cold air behind the front. Model simulations with specified surface temperature differences confirm the importance of upward heat flux from the surface in slowing the southward movement of the cold surge. It is concluded that the slowing is not due simply to the thermal wind developing in response to the heating of higher terrain to the west. Since surface heating is distributed over a deeper layer on the warm side of the temperature discontinuity, there is frontolysis at the surface. But this modification would develop even over flat terrain. Sloping terrain introduces additional effects. Heating at the western, upslope side of the cold surge inhibits the development of pressure gradients favorable to northerly flow. A second contribution comes from westerly winds at ridgetop level. These winds are heated over the higher terrain and flow downslope, further retarding the progression of the cold air at the surface.
December 1987.
Keywords: Cold waves (Meteorology) -- Colorado